Qualidade da carne bovina submetida à marinação com própolis verde, vermelha e marrom - Assis, Ana Paula Pinheiro de (Universidade Federal Rural do Semi-Árido, 2020)
The objective of this work was to evaluate the effect of marinades enriched with extracts of green, red and brown propolis on the quality characteristics of beef over 12 days of cold storage (4 ° C ± 1 °). Portions of the fillet (Longissimus dorsi) marinated with distilled water (control), marinated with green propolis (MGP), red propolis (MRP) and brown propolis (MBP) were used. For microbiological analysis, the samples were subjected to the determination of mesophilic, psychrotrophic, psychrophilic and salmonella spp. The physicochemical parameters of pH, color (L * a * b *), water holding capacity (CRA), cooking weight loss (PPC), shear strength (FC), moisture, ash, protein were evaluated , lipids and lipid oxidation. The analyzes were performed in triplicate at times: 0 3, 6, 9 and 12 days. For the sensory analysis, acceptance and purchase intention tests were performed. Microbiological analyzes showed that the samples met the microbiological standards for fresh meat, the presence of Salmonella sp. in any of the samples during cold storage. For pH values, samples marinated with MRP maintained an acceptable pH for consumption. MRP and MBP offer protection that prevents losses, showing CRA values of 74.53 and 71.77%, respectively on the 12th day of storage. MGP showed less weight loss in cooking on the 12th day of storage and also showed lower values of shear force. The MGP and MBP samples showed smaller changes in the luminosity values. The extracts maintained the values of moisture, ash, protein and lipids stable, and delayed lipid oxidation throughout the storage period. As for the sensory test, the least accepted marination was the MRP because it had a strong taste and odor. The purchase intention by the judges showed that the MBP meat had a higher percentage of purchase intention (70%). Red propolis has shown potential use as a food preservative, but has a strong and unpleasant taste that alters sensory characteristics. Meat marinated with brown propolis showed a higher purchase intention by the evaluators, also showing higher marks in the acceptance test. The use of the extracts showed antioxidant and antimicrobial capacity, thus preserving the physical-chemical and microbiological characteristics of the meat and the marinating with the brown propolis extract was the most accepted by the tasters
Keywords: Características físico-químicas; Conservação da carne; Intenção de compra; Vida de prateleira; Physical-chemical characteristics; Meat conservation; Purchase intention; Shelf life; CIENCIAS AGRARIAS::MEDICINA VETERINARIA